Low magnitude high frequency vibration induces RANKL via cyclooxygenase pathway in human periodontal ligament cells in vitro - Sutiwa Benjakul; Chidchanok Leethanakul; Suwanna Jitpukdeebodintra (Journal of Oral Biology and Craniofacial Research)
Objective: This study aimed to examine the effects of PGE2 on RANKL expression in response to vibration and vibration in combination with compressive stress and characterise this transduction pathway in periodontal ligament (PDL) cells. Methods: Cultured human PDL cells obtained from extracted premolar teeth (from six individuals) were subjected to three cycles of vibration (0.3 g, 30 Hz for 20 min every 24 h; V), compressive stress (1.5 g/cm2, 48 h; C) or vibration in combination with compressive stress (VC). To investigate whether the expression of RANKL and PGE2 was COX-dependent, PDL cells were treated with indomethacin prior to the onset of mechanical stimulation. RANKL and OPG expressions were examined by quantitative real-time polymerase chain reaction (qPCR). Quantification of PGE2, soluble RANKL (sRANKL) and OPG productions were measured using enzyme-linked immunosorbent assay (ELISAs). Results: All mechanical stresses (V, C and VC) significantly increased PGE2 and RANKL. OPG was not affected by vibration, but was downregulated in compressed cells (C and VC). Indomethacin abolished induction of RANKL and downregulated OPG in response to all mechanical stresses. Conclusion: These results suggest that vibration, compressive stress and vibration in combination with compressive stress induce RANKL expression in human PDL cells by activating the cyclooxygenase pathway.